Prioritisation of 14 quality management tools based on quality principles using integrated approach of multi-criteria decision-making and importance-performance analysis - the case of Marjan Tile Company. (2016) - Goharshenasan, Ali; Shahin, Arash; Esmaelian, Majid
The aim of this research is to propose a framework for classifying 14 quality management tools based on quality principles. For this purpose, multi-criteria decision-making, importance performance analysis and a survey on 13 process owners of Marjan Tile Company have been conducted. Based on the findings, three packages have been proposed for quality management tools as: 1) relation diagram and process decisions planning chart; 2) check sheets, Pareto diagram, cause and effect diagram, histograms and tree diagram; 3) control chart, procedure diagram, matrix analysis of data, matrix diagrams, scatter diagram, affinity diagram and diagram of concentration of defects.